The use of psychotropic substances among students: The prevalence, factor association, and abuse - Che Fadhilah bt Mamat; Shazia Qasim Jamshed; Tarek El Syed; Tahir Mehmood Khan; Noordin Othman; Abdul Kareem Al-Shami; Syahrir Bin Zaini; Mohammad Jamshed Siddiqui (Wolters Kluwer Medknow Publications, 2015)
This detailed review analyzed the previously published studies related to the prevalence of psychotropic substances use, associated factors, and the misuse of the psychotropics among students. A comprehensive literature search covering six databases was performed. References from published articles and reports were extracted. This helped in identifying the available information on the use of psychotropic drugs. A total of 16 articles were included in this review. There is an upsurge of using psychotropics with the preceding years. More students are exposed to the risk of using psychotropic substances due to the multiple factors like stress, increased academic workload, etc. The misuse is found to be common with prescribed psychotropic substances. Students need to be aware of the bad outcomes of using psychotropic substances. Participation of every stakeholder to curb this menace needs to be emphasized. More extensive studies are required to know about the increasing prevalence, factors, and misuse of psychotropics.